Laser production of gas phase complexes of metal α-aminophosphonic acid mixtures and their role in chiral recognition. (2001) - Paladini, A.; Calcagni, C.; Palma, T. Di.; Satta, M.; Speranza, M.; Scuderi, D.; Laganà, A.; Fago, G.; Guidoni, A. Giardini
Abstract : Clusters between first-group metal ions and chiralα -aminophosphonic acids have been readily generated by Pulsed Laser Ablation (PLA) and by Electrospray Ionization (ESI) and their fragmentation investigated by mass spectrometry. The complexes studied have the general formula[ Me ( I ) Cl 2 ] +, where Me(I) is H, Li, Na, or K, C is ( R )-(—)- (1-aminoethyl) phosphonic acid (E R ) and (S)-(+)-(1-aminoethyl) phosphonic acid (E S ), (1R)-(+)-(1-amino-2-methylpropyl) phosphonic acid (P R ) and (1S)-(—)-(1-amino-2-methylpropyl) phosphonic acid (P S ), (1R)-(-)-(1-amino-hexyl) phosphonic acid ( H R ) and (1S)-(+)-(1-amino-hexyl) phosphonic acid ( H S ), o-phospho-L-serine ( S S ) and o-phospho-D-serine (S R ), and L is a referenceα -aminophosphonic acid (E, P, H or S) of defined configuration. Collision induced dissociation (CID) of diastereomeric[ Me ( I ) Cl 2 ] + complexes leads to fragmentation patterns characterized by[ Me ( I ) Cl ] + / [ Me ( I ) L 2 ] + abundance ratios which depend upon the configuration of solute C. These different spectral features were correlated to the different stability of the diastereomeric[ Me ( I ) C R L ] + and[ Me ( I ) C S L ] + complexes in the gas phase.